Pandemirespons og global helse i norsk utenrikspolitikk – og i FNs sikkerhetsråd - Halvorsen, Audun (Internasjonal Politikk, 2021)
Global helse har stått sentralt i norsk utenriks-, utviklings- og helsepolitikk i en årrekke. Norge er anerkjent som en synlig aktør på global helse gjennom vesentlige finansielle bidrag, men også som en aktør som har bidratt til etablering av nye institusjoner og mekanismer som vaksinealliansen Gavi, Global Financing Facility for Women, Children and Adolescents (GFF) og Coalition for Epidemic Preparedness Innovations (CEPI). Norge spiller også en aktiv rolle i det internasjonale helsepolitiske samarbeidet, og er en aktiv deltaker i Verdens helseorganisasjon (WHO). Norge er – og har vært – gjenkjennelig på global helse over lang tid, og i alle internasjonale fora. Vi mener det er viktig å bidra til – og sikre – at konsekvensene av pandemier og globale helseutfordringer på internasjonal fred og sikkerhet også hører hjemme på dagsordenen til FNs sikkerhetsråd. Abstract in English: Pandemic Response and Global Health in Norwegian Foreign Policy – and in the UN Security Council Global health has been a priority for Norway and for Norwegian foreign, development and health policies for the past decades. Norway is recognized as an active and consistent partner in global health questions, both through substantial financial contributions and as an advocate for establishing new institutions and mechanisms such as Gavi (the Vaccine Alliance), the Global Financing Facility for Women, Children and Adolescents (GFF) and the Coalition for Epidemic Preparedness Innovations (CEPI). Norway is also playing a leading role in the international cooperation in global health issues and in promoting a coordinated and effective humanitarian response to the COVID-19 pandemic. Norway actively participates and firmly supports the leading role played by the World Health Organization (WHO) in this regard. Norway will continue to be a consistent and recognizable partner in global health issues in all international fora. We firmly believe that it is important to contribute to – and secure – that the implications of pandemics and global health crises can be seen as threats to international peace and security and thus belong on the agenda of the UN Security Council.